Cerebral A-V Malformation in Neonate - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A baby girl who developed congestive heart failure at 3 days of age and was shown to have an aneurysm of the vein of Galen is reported from the Dept Child Health, The Queen's Univ Belfast, Royal Maternity Hosp and Dept Radiology, Royal Victoria Hosp, Belfast.